The young massive star cluster westerlund 2 observed with MUSE: II. MUSEpack; a python package to analyze the kinematics of young star clusters - Zeidler, Peter; Grebel, Eva K.; Pasquali, Anna (The astronomical journal, 2019)
We mapped the Galactic young massive star cluster Westerlund 2 with the integral field spectrograph MUSE (spatial resolution: 0.2 arcsec px−1, spectral resolution: Δλ = 1.25 Å, wavelength range: 4600-9350 Å) mounted on the Very Large Telescope. We present the fully reduced data set and introduce our new Python package “MUSEpack,” which we developed to measure stellar radial velocities (RVs) with an absolute precision of 1-2 km s−1 without the necessity of a spectral template library. This novel method uses the two-dimensional spectra and an atomic transition line library to create templates around strong absorption lines for each individual star. Automatic, multi-core processing makes it possible to efficiently determine stellar RVs of a large number of stars with the necessary precision to measure the velocity dispersion of young star clusters. MUSEpack also provides an enhanced method for removing telluric lines in crowded fields without sky exposures, and a Python wrapper for ESO’s data reduction pipeline. We observed Westerlund 2 with a total of 11 short and 5 long exposures (survey area: ∼11 arcmin2 or 15.8 pc2) to cover the bright nebular emission and OB stars, as well as the fainter pre-main-sequence stars (≥1 M ⊙). We extracted 1725 stellar spectra with a mean signal-to-noise ratio of S/N > 5 per pixel. Typical RV uncertainties of 4.78 km s−1, 2.92 km s−1, and 1.1 km s−1 are reached for stars with a mean S/N > 10, S/N > 20, and S/N > 50 per pixel, respectively. It is possible to reach RV accuracies of 0.9 km s−1, 1.3 km s−1, and 2.2 km s−1 with ≥5, 3-4, and 1-2 spectral lines used to measure the RVs, respectively. The combined statistical uncertainty on the RV measurements is 1.10 km s−1.